Biochemical and anatomical characteristics associated with browning of Bambusa lako Widjaja (Poaceae) in vitro shoot explants - Andrea Holst; Paula Carvajal-Campos; Yanely Marisol Canales-Ochoa; Andrea Irías-Mata; Laura Vega-Fernández; Miguel Benavides-Acevedo; Paul Solórzano-Cascante; Víctor M. Jiménez (Advances in Bamboo Science)
Browning is a limiting factor for the successful propagation of several, mainly woody, plant species through tissue culture. Bamboos are not exempt from this constraint, which has been described as particularly critical for the micropropagation of several Bambusa species, such as B. lako. To understand the browning process in this species, we investigated whether the browning of in vitro nodal explants was linked to the accumulation of phenolic compounds, polyphenol oxidase activity, and oxidative stress as indicated by the presence of malondialdehyde. A four-point Browning Gradient Index was developed to evaluate these biochemical parameters. We observed an increase in the concentration of total phenolics, polyphenol oxidase activity, and malondialdehyde levels between green and fully brown grades. Histological analysis revealed a greater accumulation of protein in the green shoots compared to brown tissues. Polyphenols and peroxidase were localized in the vascular bundles in all browning grades.